Inequality Act Faced by The Main Character in Novel Kim Ji Young, Born 1982: A Gender Based Study - Dinda Alfarini; Morada Tetty (Universitas Negeri Medan, 2022)
This study aims to analyze Gender Inequality based on Gender Study of the main character in novel Kim Ji Young, Born 1982. This research was conducted by applying the textual analysis method. The data source is taken from the novel by Cho Nam Joo, entitled Kim Ji Young, Born 1982 which was translated into English by Jamie Chang. This study used the theory of Gender Inequality by Sylvia Walby (1990) and that there are 6 types of gender inequality, namely household production, paid work, the patriarchal state, male violence, sexuality and culture. The results show all types about gender inequality by Walby can be found in the novel and the main character struggles to face the inequality act that she experiences is the depression she experiences which changes her personality.